DETECTION OF EMOTIONAL SENSITIVITY USING FUNCTIONAL NEAR INFRARED SPECTROSCOPY BASED DYNAMIC FUNCTIONAL CONNECTIVITY - SHENG, CHONG JIE (2021)
Recent studies have applied neuroimaging for emotion recognition, but little is known about how it may help assess the development of emotion sensitivity